(untitled) (European Journal of Pure and Applied Mathematics, 2018)
The goal of this paper is to provide a mathematical model which based on numerical simulation applied to heat equationsÂ and comparing the obtained results with virtualÂ temperatures results for different depths of the homogeneous agricultural soil. TheÂ model was treated through this research that enable to know the degree of soil temperature homogeneous without recourse to tools ofÂ measuring physical expensive. The importance of this lies in the agricultural seed germination at temperatures suitable.